IFPRI's nutrition research in West Africa at a glance - Poverty, Health, & Nutrition Division (International Food Policy Research Institute, 2017)
Our research aims to improve nutrition by understanding and addressing both the direct determinants of malnutrition (such as diets, caregiving and feeding practices, and health) and the underlying contributors (such as income, food security, education, gender equity, and access to health, hygiene, and sanitation services). This work seeks to increase the nutrition sensitivity of programs and policies in a wide range of relevant sectors (including agriculture, social protection, and health) by ensuring that they incorporate specific nutrition goals and actions, such as behavior change communication, interventions to improve access to micronutrient-rich foods and high-quality diets, or strategies to reduce health risks. IFPRI also works to enhance the gender sensitivity of development programs and policies, recognizing the unique role that women can play in ensuring household food security and prioritizing the nutrition, health, and education of their children.